Olhar dos moradores da Comunidade Estirão Comprido sobre as mudanças ocorridas no Rio Cuiabá - MT - Santos, Ingrid Regina da Silva (2014)
Water is one of the most controversial in terms of natural resource use and conservation, due to its complexity, occasioned by the exercise of its different forms, representations and functions. It appears from this diversity as favoring the growing conflicts, which have different fronts, among them the changes occurring in a water environment, this being the Cuiabá River, which, in short, presents in its route from upstream to downstream, a wide variety in terms of use and occupation. Worried about what this diversity is in terms of changes, this research aims to identify, through perception, changes in Cuiabá River and how they reflect the way of life of coastal. To this end, we chose to address it from the perspective of the residents of Estirão Comprido Traditional Community, located in the municipality of Barão Melgaço state of Mato Grosso. Understanding that perceptions are linked to personal experiences, we seek to place the concept of the theoretical and geographical contribution to the discussion on the relations established between community residents and the Cuiabá River, which made possible the construction of knowledge which enabled the detection of changes occurring in this environment. The identification of relations of community residents with the Cuiabá River was based on cultural anthropology and fieldwork, developed over the years 2012 and 2013, which enabled the participant observation. As a result, it was found that all community residents have direct and / or indirect links with the river, because, it remove the fish, their main food source and economic. It is through him that also move and dessedentam, ie the Cuiabá River is the ultimate representation of the reproduction of their way of life. Understanding the meaning of this connection, it was possible to detect and engage the concerns in terms of the importance of the environment and conservation of this water resource. In this context, we find that the bordering Estirão Comprido, from what understand how the environment and environmental degradation, can reflect and identify aspects of changes in the Cuiabá River and reflections on the life of the community.